Phytochemical Analysis and in vitro Cell Viability Effects of Ethanolic Extract of Ormocarpum cochinchinense on Mouse Embryonic Fibroblasts - Somashekar, Gayathri; Sudhakar, Uma; Srividya, Seshadri; Suresh, Snophia (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Ormocarpum cochinchinense is a medicinal herb known to be used by traditional bone setters for the healing of bone fractures. This herb has many active biomolecules, which are responsible for biological activities like antioxidant, anti-inflammatory, hepatoprotective and anticancer. This study aimed to perform phytochemical screening to identify the phytoconstituents and determine the cell viability effects of ethanolic extract of Ormocarpum cochinchinense through MTT assay. Materials and Methods: Ethanolic extract of leaves of Ormocarpum cochinchinense were subjected to qualitative phytochemical screening through Gas chromatography-Mass spectroscopy analysis. The in-vitro cell viability effects on 3T3 cell lines with varying concentrations of ethanolic plant extract were measured through (3- [4, 5- dimethylthiazol-2-yl]-2, 5-diphenyl tetrazolium bromide) MTT assay. Results: Phytochemical screening identified 24 bioactive phytocompounds with various biologic activities. The herb’s in vitro cell viability effects of ethanolic extract revealed an IC50 value of 58.05µg/ml on 3T3 cell lines. Conclusion: It can be suggested that ethanolic extract of leaves of Ormocarpum cochinchinense are a potential source of bioactive phytoconstituents and are safe on 3T3 cell lines at lower concentrations. The results of this study provide scientific knowledge about the herb that may be applied in future biomedical research investigations.
Keywords: Ormocarpum cochinchinense; MTT assay; GC-MS; Phytocompounds